2004
DOI: 10.1159/000082035
|View full text |Cite
|
Sign up to set email alerts
|

Different Perceived Foreign Accents in One Patient after Prerolandic Hematoma

Abstract: Foreign accent syndrome (FAS), a rare disorder characterized by the emergence of a new accent perceived as foreign by listeners, is usually reported with left brain damage. We here report the case of a 28-year-old native Brazilian who appeared, to the examiner, to show a North American accent during recovery from Broca’s aphasia. The lesion was due to a frontal hematoma. Without referring specifically to speech, we asked 10 independent observers to comment on a videotape of the patient’s interview. Seven repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…For similar reasons, others have suggested that some cases of FAS may be mild forms or a subtype of AOS (Duffy, 2005;Whiteside & Varley, 1998). Numerous cases in the FAS literature are described as having evolved from nonfluent aphasia and/or AOS, or as including residual symptoms of these disorders (Ardila et al, 1988;Christoph et al, 2004;Graff-Radford, Cooper, Colsher, & Damasio, 1986;Ingram et al, 1992;Varley et al, 2006). In one case the foreign accent evolved to AOS during recovery from a left hemisphere stroke (Marië n et al, 2006).…”
Section: Differential Speech Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…For similar reasons, others have suggested that some cases of FAS may be mild forms or a subtype of AOS (Duffy, 2005;Whiteside & Varley, 1998). Numerous cases in the FAS literature are described as having evolved from nonfluent aphasia and/or AOS, or as including residual symptoms of these disorders (Ardila et al, 1988;Christoph et al, 2004;Graff-Radford, Cooper, Colsher, & Damasio, 1986;Ingram et al, 1992;Varley et al, 2006). In one case the foreign accent evolved to AOS during recovery from a left hemisphere stroke (Marië n et al, 2006).…”
Section: Differential Speech Diagnosismentioning
confidence: 99%
“…A review of these cases shows that the etiology and presenting symptoms of FAS are far from uniform. Despite good agreement among listeners that the accent sounds ''foreign,'' there is typically poor agreement as to the language associated with the accent (e.g., Blumstein, Alexander, Ryalls, Katz, & Dworetzky, 1987;Christoph et al, 2004;Gurd, Bessel, Bladon, & Bamford, 1988;Ingram, McCormack, & Kennedy, 1992). Detailed phonetic analyses of speech patterns have revealed allophonic variations that are atypical of the speakers' native language, particularly in prosody and vowel quality, but the unavailability of similar measures from the individuals' normal speech limits conclusions regarding the precise nature of the changes.…”
Section: Speech Characteristicsmentioning
confidence: 99%
“…At the suprasegmental level, neurogenic FAS has often been noted to have a fundamental change of speech rhythm which is described as slow (Ardila, Rosselli, & Ardila, 1988), different (Christoph, de Freitas, dos Santos, Lima, Araujo, & Carota, 2004), isosyllabic (Berthier, Ruiz, Massone, Startkstein, & Leiguarda, 1991), staccato (Berthier et al, 1991), scanning (Mariën et al, 2006) or syllable-timed (Mariën & Verhoeven, 2007). In addition to changes in speech rhythm, occasional problems with word stress placement are sometimes observed (Gurd, Bessell, Bladon, & Bamford, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, FAS is most commonly associated with lefthemisphere lesions [1] secondary to CVA [2][3][4][5][6][7][8][9][10][11][12][13] and traumatic brain injury (TBI) [14][15][16][17]. The condition is often preceded or accompanied by other communication disorders such as aphasia, dysarthria, and apraxia of speech [18].…”
Section: Introductionmentioning
confidence: 99%